Sympathy and transatlantic literature : place, genre, and emigration - Hales, Ashley Anderson (The University of Edinburgh, 2014)
This thesis posits Enlightenment articulations of sympathy, in its capacity for establishing connections and its failures, as an appropriate methodology to articulate transatlantic literary exchange. Focusing on the sympathetic gap, the space sympathy must traverse, this thesis investigates the effect of emigration and place on genre and follows the trajectory from documentary to fictive forms and from a small gap to one unable to be bridged. Because the gap of sympathy is a spatial argument, the distance between is crucial as it indicates relationship. The introduction outlines my argument, with particular attention to transatlantic criticism, what is meant by the gap of sympathy, and the triad of place, emigration and genre. The first chapter discusses how Adam Smith articulated how one person is able to maintain a stable identity and is able to connect with another through imaginative comparison. The chapter establishes the trajectory of sympathy as the gap moves from smallest to unbridgeable, through comparison, sympathy and the failure of sympathy. In a series of case studies, Chapters Two through Five test out Smith’s theories in literary works; they examine the trajectory of transatlantic sympathy, where the gap moves from rhetorically being small to gaping, and moves generically from documentary forms to fiction. Chapter Two uses emigration guides written by British emigrants, who, because of their emigrant status, write from both an American and British perspective. The guides, because of their promotional intent, tend to underplay the gap of sympathy. Although they could be read as documentary and objective, the guides evidence ideological and rhetorical similarities to transatlantic fiction and thus serve as an entrance into the themes and stylistics one tends to associate with literary genres. Chapter Three examines the transatlantic correspondence of the Kerr family. As the Kerr family corresponds transatlantically (separated in space by the Atlantic and in time by more than 50 years), the issue of space becomes paramount to understanding the correspondence as well as if sympathy works in this generic register. Generically, the transatlantic letter is meant to provide virtual presence amid long stretches of absence; it also becomes an analogue for the absent other and the means by which the family may continue to be imagined across the gap of sympathy. Chapter Four examines Susanna Rowson’s transatlantic works, particularly Charlotte Temple, Slaves in Algiers, and Reuben and Rachel. Rowson’s own emigrant experience provides an entrée to the pain of transcultural sympathy that we see most clearly in Reuben and Rachel. Throughout her works Rowson also advocates a sympathy that is active and moral, rather than emotionally vacuous. Reuben and Rachel illustrates the gap of sympathy being bridged most effectively in cross-cultural adaptations and yet finally settles for a sympathy that must acknowledge separation and difference as well. Chapter Five explores the failures of sympathy and sociability present in Charles Brockden Brown’s gothic novels, Wieland and Edgar Huntly. Characters’ frontier locations and claustrophobic versions of sociability, as well generically, the gothic turn and failure of epistolary exchange, signals the moral ambiguity connected with becoming ‘this new man’ of America. Brown’s epistolary fiction briefly considered offers another generic attempt to examine how the gap of sympathy may be bridged and extend beyond the confines of the family. The Afterword points to the total breakdown of sympathy as a turn inward and away from sociability, where the self becomes frantic and frenetic (as evidenced by Crèvecoeur’s Letters from an American Farmer); it points to some useful applications to the gap of sympathy for transatlantic literary studies.
Keywords: sympathy; transatlantic literature; emigration; genre